2017
DOI: 10.1002/mp.12215
|View full text |Cite
|
Sign up to set email alerts
|

The potential of dual-energy CT to reduce proton beam range uncertainties

Abstract: DECT has a clear potential to improve proton beam range predictions over SECT in proton therapy. However, in the current state high levels of noise remain problematic for DECT characterization methods and do not allow getting the full benefits of this technology. Future work should focus on adapting DECT methods to noise and investigate methods based on raw-data to reduce CT artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
141
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 29 publications
(67 reference statements)
2
141
0
Order By: Relevance
“…This arises because the sampled range errors in voxels of equal length are influenced by SPR errors and this aspect is discussed in section 4 of Ref. . This result also supports with the findings of Bornefalk who suggested that the intrinsic dimensionality of low‐Z elements at diagnostic energies is four.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…This arises because the sampled range errors in voxels of equal length are influenced by SPR errors and this aspect is discussed in section 4 of Ref. . This result also supports with the findings of Bornefalk who suggested that the intrinsic dimensionality of low‐Z elements at diagnostic energies is four.…”
Section: Discussionsupporting
confidence: 84%
“…That is,Znormalmedtrueσ^e,Z1false(σnormale,normalmedfalse).For a postcalibration measurement, the estimator of Zmed is given by:trueZ^normalmed=false∑j=1JcjnormalΓj1where Γ is a quantity independent of electron density, being either the dual‐energy index or dual‐energy ratio, and cj are calibration coefficients. In this study, we use J =3 to insure optimal robustness against noise . Based on this technique, the estimator of the ED is:trueρ^normale=ul=1LblZnormalmedl1,where bl are calibration coefficients.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations